NLRP3 Regulates IL-4 Expression in TOX+ CD4+ T Cells of Cutaneous T Cell Lymphoma to Potentially Promote Disease Progression - Huanosta-Murillo, Enrique; Alcántara-Hernández, Marcela; Hernández-Rico, Brenda; Victoria-Acosta, Georgina; Miranda-Cruz, Patricia; Domínguez-Gómez, María Antonieta; Jurado-Santacruz, Fermín; Patiño-López, Genaro; Pérez-Koldenkova, Vadim; Palma-Guzmán, Alam; Licona-Limón, Paula; Fuentes-Pananá, Ezequiel M.; et al. (Frontiers in Immunology, 2021)
In cutaneous T cell lymphoma (CTCL), a dominant Th2 profile associated with disease progression has been proposed. Moreover, although the production and regulation of IL-4 expression during the early stages of the disease may have important implications in later stages, these processes are poorly understood. Here, we demonstrate the presence of TOX+ CD4+ T cells that produce IL-4+ in early-stage skin lesions of CTCL patients and reveal a complex mechanism by which the NLRP3 receptor promotes a Th2 response by controlling IL-4 production. Unassembled NLRP3 is able to translocate to the nucleus of malignant CD4+ T cells, where it binds to the human il-4 promoter. Accordingly, IL-4 expression is decreased by knocking down and increased by promoting the nuclear localization of NLRP3. We describe a positive feedback loop in which IL-4 inhibits NLRP3 inflammasome assembly, thereby further increasing its production. IL-4 induced a potentially malignant phenotype measured based on TOX expression and proliferation. This mechanism of IL-4 regulation mediated by NLRP3 is amplified in late-stage CTCL associated with disease progression. These results indicate that NLRP3 might be a key regulator of IL-4 expression in TOX+ CD4+ T cells of CTCL patients and that this mechanism might have important implications in the progression of the disease.